Triethylated chromones with substituted naphthalenes as tubulin inhibitors - Nakagawa-Goto, Kyoko (Bioorg Med Chem, 2016)
Previously synthesized 2-(benzo[b]thiophene-3′-yl)-6,8,8-triethyldesmosdumotin B (1, TEDB-TB) and 2-(naphth-1′-yl)-6,8,8-triethyldesmosdumotin B (2) showed potent activity against multiple human tumor cell lines, including a multidrug-resistant (MDR) subline, by targeting spindle formation and/or the microtubule network. Consequently, ester analogues of hydroxylated naphthyl substituted TEBDs (3–5) were prepared and evaluated for their effects on tumor cell proliferation and on tubulin assembly. Among all new compounds, compound 6, a 4′-acetoxynaphthalen-1′-yl derivative, displayed the most potent antiproliferative activity (IC(50) 0.2–5.7 μM). Selected analogues were confirmed to be tubulin assembly inhibitors in cell-free and cell-based assays using MDR tumor cells. The new analogues partially inhibited colchicine binding to tubulin, suggesting their binding mode would be different from that of colchicine. This observation was supported by computational docking model analyses. Thus, the newly synthesized triethylated chromones with esterified naphthalene groups have good potential for development as a new class of mitotic inhibitors that target tubulin.